From The First Comporate Accounting Practices İn The Ottoman Empire: Ereğli Coal Company And Accounting Book Racords XIXth Century - Toraman, Cengiz; Öğreten, Ahmet (Eleventh World Congress of Accounting Historians Nantes, France, July 19-22, 2006, 2006)
In the Ottoman Empire traditional bookkeeping style was employed up until the end of the 19th century. This style, developed uniquely by the Ottomans, was in no way related to simple entry account keeping method of the west. Accounting records of the Eregli Coal Company which was one of the first modern corporations in the Ottoman Empire were kept in this traditional system. The purpose of this study is to give information about Eregli Coal Company and its activities. Accounting records of this company, which was established by six national partners, for the first period of operations covering over 3 years between November 1842 to November 1845 are examined towards this end. With Sultan Abdttlmecid's participation as share holder the company was renamed the New Company and continued its activities until the control of Eregli coal basin was transferred to the Ministry of the Navy. Investigation of first period accounting records show that the main factor contributing to the losses incurred by the Company is the sale of coal to government owned enterprises and high interest loans incurredfrom bankers as a result of these uncollectible credits.
Keywords: Accounting, coal, company, hazine-i hassa, income statement